Influence of Age and Cognitive Reserve on Cognitive Function in HIV-infected South African Adults - Wagner, Marcelle (Department of Psychology, 2022)
Background. HIV remains a significant global public health concern. South Africa is one of the hardest-hit countries, housing more than 7 million people living with HIV (PLWH), a figure that represents more than 12% of the global infected population. Globally, HIV-associated cognitive impairment is present in almost 45% of PLWH, with 72% of that total burden found in Sub-Saharan Africa (Wang et al., 2020). The severity and trajectory of that impairment is, however, influenced by numerous risk and protective factors. This study aimed to investigate the strength of influence that two of these factors (cognitive reserve and age) have in a sample of HIV-positive South African adults. Method. Participants were 32 HIV-infected and virally suppressed adults (27 women; Mage = 41.13±9.34). They were administered the Cognitive Reserve Index Questionnaire (CRIq) and a comprehensive neuropsychological battery that assessed performance on tests of motor function, attention and working memory, information processing speed, language, memory, and executive function. They also provided 3T magnetic resonance imaging data. Bivariate correlations, independent-sample t-tests, and hierarchical regression models tested the prediction that age and cognitive reserve (as indexed by CRIq scores, fractional anisotropy, white and gray matter volume, education level, and IQ score), both independently and in interaction, will have significant effects on cognitive test performance (i.e., that increasing age and lower levels of cognitive reserve will be independently associated with poorer performance, and that older adults with lower levels of cognitive reserve will display the worst performance). Results. Regarding the association of age with global cognitive function (average performance across all tests), analyses detected a moderate negative correlation (r = -.425, p = .015.), a significant between-group difference (participants ≥ 45 years worse than those < 45 years, p = .012), and a significant proportion of variance accounted for (R 2 = .18, p = .016). There were no significant main effects of cognitive reserve, and no significant age x cognitive reserve interaction effect, on cognitive test performance. Conclusion. The current analyses confirmed the influence of age on cognition in PLWH but did not provide support for the same influence of cognitive reserve. Although neuroscience research attaches increasing importance to the construct of cognitive reserve, the lack of a universally-applied definition (and hence a standard measure) of the construct hampers investigations such as this and makes cross-study comparisons difficult. From a policy-making perspective, the contrasting findings regarding age and cognitive reserve is crucial because it is imperative that intervention efforts focus only on those modifiable factors that significantly impact cognitive function, especially in countries such as South Africa that are characterized by high HIV disease burden and limited clinical and infrastructural resources.